“Vsyo ne tak, kak nado…”: from Vysotsky’s parody to Pyetzukh’s remake (axiologisation of Russian classic) - Chavdarova, Dechka (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2021)
The idea of the literariness of Russian culture, of the impact of literature on Russian life may be an axiom of the Russian cultural consciousness, yet it does not cease to attract the attention of researchers. Russian literature itself, from the 19th century onwards, has been a manifestation of this idea, even though the semantics of the life–literature relationship evolves. The present text traces the development of the said idea in the Russian unofficial literature from the Soviet period (1960s-1980s) on the basis of comparison between Vladimir Vysotsky’s parody on Pushkin’s prologue to the poem Ruslan and Lyudmila and Vyacheslav Pyetzukh’s The New Moscow Philosophy (Novaya moskovskaya filosofiya) – a remake of Dostoevsky’s Crime and Punishment. A question is posed about the difference between Vysotsky’s parody and school parodies (a connection which the bard’s researchers also investigate) and the elements of remake within it. The analysis thus leads to the theoretical problem of the relationship between parody and remake. What calls for attention in Pyetzukh’s novella is the metatextual commentary on the role and value of the Russian classics (and literature in general), and on the literariness of the Russian consciousness – a commentary which becomes close to scientific discourse. The affinity of Pyetzukh’s concept with that of Vysotsky can also be found in the travestied image of the Soviet reality as seen in the mirror of a classic work, and in the direct expression of the notion of devaluation: the “not as with other people” formula in Pyetzukh, and the one “things are not as they ought to be” in Vysotsky. The conclusion points to the development of a similar axiologisation of the Russian classics observable in the post-modern remakes from the 1990s to this day.